Smart Glasses / Nor Shamyza Azrin Azmi - Azmi, Nor Shamyza Azrin (2020)
Israk optical which is a smart glasses, is a product that is needed to be invented and introduced for consumers. This product was targeted to small and large scale customers such as travellers, workers and teenagers. Generally, smart glasses aim to provide life monitoring services, as well as creating a platform for taking more authentic photos and video clips. They can also be equipped with augmented reality technology, intended to assist you with your everyday home and business life. Smart glasses work through a combination of display, sensors and accelerometers, coupled with smart software and internet connectivity to make them really useful. They tend to come with touchpads and/or voice controls to help users navigate the software that powers them, which can be embedded into the glasses themselves or incorporated into a handset – or both.